A case report on pituitary tuberculosis (Bangladesh Journal of Medical Science, 2024)
Tuberculosis is an infectious disease that involves any organ.  However,  the  primary  pituitary  tuberculosis  is an  extremely  rare  disease.  Intracranial  tuberculomas account  for  0.15-5%  of  intracranial  space-occupying lesions,  of  which,  pituitary  as  the  primary  site is  unusual,  and  easily  misdiagnosed  as  pituitary adenoma. In this setting, the late diagnosis can result in  permanent  endocrine  dysfunction.  We  report the  case  of  a  28-year-old  woman  who  presented  to the  endocrinology  department  with  complaints  of progressively  increasing  headache  for  1  month  and double vision. On the clinical examination, the patient was conscious and oriented. The routine hematological and  biochemical  workup  showed  an  increased erythrocyte  sedimentation  rate  (ESR)  and  increased prolactin  levels.  MRI  scan  of  Brain  reveals  Pituitary macroadenoma  with  impingement  upon  the  optic chaisma,  no  other  significant  abnormality  is  detected in  the  brain.    No  other  radiological  and/or  clinical clue  that  could  elicit  the  suspicion  of  pulmonary  or extrapulmonary  lesions  of  tuberculosis  was  found. The  Endoscopic  Transnasal  Transphenoidal  Surgery was  done.  The  histopathological  examination  of multiple  irregular  tissue  from  excised  tumor  was Granulomatous  inflammation  and  the  final  diagnosis of  pituitary  tuberculoma  was  made.  We  report  this rare  case  of  pituitary  lesion  that  may  be  included  in the  differential  diagnosis  of  sellar  lesions  to  avoid unnecessary  surgical  interventions,  especially  in regions where the disease is endemic.Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 864-868